Numerical Models of Hierarchical Threshold Secret Sharing and Broadcasting with Encryption - Kapusta, Joanna; Smarzewski, Ryszard (Wydawnictwo Politechniki Łódzkiej, 2018)
In the paper there are presented two new models of encrypted hierarchical secret sharing schemes based on barycentric Hermite formula. Moreover an application of the second scheme to design a novel broadcast encryption protocol is proposed. The protocol allows to send a decoding key to any user via broadcast channel and revoke some users without the necessity of updating encrypted private keys of the other users of the system. To ensure the safety of user private keys the protocol uses one-way functions that fulﬁll special conditions.
Keywords: hierarchical secret sharing; barycentric Hermite weights; broadcast; encryption; hierarchiczne udostępnianie tajnych informacji; barycentryczne ciężarki Hermite; nadawanie; szyfrowanie